UNRAVELING THE GENETIC AND BIOLOGICAL INTRICACIES OF ANESTHESIA FOR CHRONIC PAIN: A COMPREHENSIVE REVIEW OF COMT GENE VARIATIONS AND THEIR IMPACT ON TREATMENT EFFICACY ACROSS ETHNICITIES - Arruda, Rafael Augusto Jesus; Destefani, Vinícius Côgo; Destefani, Afrânio Côgo (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2024)
Chronic pain management remains a significant challenge, with individual responses to anesthesia and analgesics varying widely due to genetic and biological factors. This review explores the influence of the catechol-O-methyltransferase (COMT) gene, particularly the Val158Met polymorphism, on pain sensitivity and opioid efficacy across different ethnicities. COMT variations play a crucial role in modulating pain perception and analgesic response, with Met allele carriers generally exhibiting higher pain sensitivity and lower opioid requirements. Ethnic differences in COMT gene frequencies further impact anesthesia efficacy, underscoring the importance of personalized pain management strategies. The review also discusses the potential of pharmacogenetic approaches, a beacon of hope for improving treatment outcomes. It highlights emerging technologies in genetic-based pain management, such as epigenetic modulation and gene editing.